Pemberdayaan Masyarakat Desa Sendangarum DIY dalam Mempersiapkan Pembentukan Badan Usaha Milik Desa (BUMDes) - Sakir Sakir; Bhakti Gusti Walinegoro; Herpita Wahyuni (Jurnal Surya Masyarakat, 2022)
The Real Work Lecture Program (KKN) of the University of Muhammadiyah Yogyakarta provides support for the establishment of Village Owned Enterprises (BUMDes). The benefits of BUMDes are to improve the village and community economy, increase original village income, and improve potential village management according to community needs and economic equity. The implementation of the Community Service Program was held in Sendangarum Village, Sleman, Yogyakarta Special Region, from October 15 to December 15, 2021, in the context of community service, which aims to optimize the potential and progress of the village by preparing villages to form BUMDes. The method of implementing the program is by socializing the importance of establishing BUMDes, making complete information about villages through making village profiles that are useful as village introductions, and exploring village potential. The appearance of an attractive Instagram logo and social media is a strategy to increase product sales packaged in preparing for the formation of BUMDes. Assistance and training with training on institutional aspects of BUMDes, BUMDes Innovation Training, BUMDes Digitization Training, and BUMDes Sustainability Training help prepare for the formation of (BUMDes). Mentoring and training facilitated by the University of Muhammadiyah Yogyakarta support realizing the ideals of Sendangarum Village to have a BUMDes.